Nutritional status of young female elite gymnasts - Lopez-Varela, S.; Montero, A.; Chandra, R. K.; Marcos, A. (International Journal for Vitamin and Nutrition Research, 2000)
The purpose of this study was to evaluate the nutritional status of a group of 10 young female elite gymnasts aged 13-17 years, who do a physical exercise of 48 h/wk. Assessment included dietary intake for 7 days, body mass index, ideal body weight, and skinfold thickness. In addition, the number of total leukocytes, total lymphocytes and lymphocyte subsets CD2, CD3, CD4, CD8, CD19 and CD56 were counted. The results were compared with a control group consisting of 50 volunteer students doing less than 12 h/wk of physical exercise, who were matched by sex, age, and sociocultural level. The total weekly calorie intake was lower in gymnasts than in controls; gymnasts showed a higher calorie intake from dietary protein together with a lower calorie intake from lipid and carbohydrate sources in comparison with controls. All the anthropometric parameters, except height which was not different in the two groups, were lower in gymnasts than in controls. The lymphocyte and leukocyte counts were also lower in gymnasts in relation to controls, except CD19 and CD56 subsets which were similar in both groups. It is suggested that gymnasts are at risk of malnutrition, which when compounded with intense physical exercise could lead to immunosuppression in these athletes.